2017
DOI: 10.1093/police/paw057
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential for Body-Worn Cameras to Reduce Violence in Police–Citizen Encounters

Abstract: One of the most compelling perceived benefits of body-worn cameras (BWCs) involves the potential for reductions in citizen complaints and police use of force. A handful of early studies reported significant reductions in both outcomes following BWC adoption, but several recent studies have failed to document such effects. The current study explores this question using data from a randomized controlled trial conducted in the Spokane (WA) Police Department. Approximately half of patrol officers (n = 82) were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
171
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(184 citation statements)
references
References 12 publications
4
171
0
2
Order By: Relevance
“…An evaluation of BWCs in the Rialto (CA) Police Department documented a nearly 90% drop in citizen complaints against police and a 60% decline in use of force by officers (Ariel et al, 2015). Similarly positive results were reported in studies of BWCs in Mesa (AZ; Mesa Police Department, 2013), Phoenix (AZ; Hedberg, Katz, and Choate, 2017), Orlando (FL; Jennings et al, 2015), Spokane (WA; White et al, 2018), Tampa (FL; Jennings et al, 2017), Las Vegas (Braga, Sousa, Coldren, and Rodriguez, 2018), and the United Kingdom (Ellis, Jenkins, and Smith, 2015;Goodall, 2007). Maskaly, Donner, Jennings, Ariel, and Sutherland (2017: 685) conducted a meta-review of more than 20 studies aimed at examining the impact of BWCs on a range of citizen and officer outcomes (e.g., use of force, citizen complaints, and citizen and officer perceptions), and the authors concluded: "The evidence seems to suggest that the police are generally receptive to BWC adoption, and that BWCs can exert positive effects on both citizen and police behavior."…”
Section: Literature Reviewmentioning
confidence: 71%
See 2 more Smart Citations
“…An evaluation of BWCs in the Rialto (CA) Police Department documented a nearly 90% drop in citizen complaints against police and a 60% decline in use of force by officers (Ariel et al, 2015). Similarly positive results were reported in studies of BWCs in Mesa (AZ; Mesa Police Department, 2013), Phoenix (AZ; Hedberg, Katz, and Choate, 2017), Orlando (FL; Jennings et al, 2015), Spokane (WA; White et al, 2018), Tampa (FL; Jennings et al, 2017), Las Vegas (Braga, Sousa, Coldren, and Rodriguez, 2018), and the United Kingdom (Ellis, Jenkins, and Smith, 2015;Goodall, 2007). Maskaly, Donner, Jennings, Ariel, and Sutherland (2017: 685) conducted a meta-review of more than 20 studies aimed at examining the impact of BWCs on a range of citizen and officer outcomes (e.g., use of force, citizen complaints, and citizen and officer perceptions), and the authors concluded: "The evidence seems to suggest that the police are generally receptive to BWC adoption, and that BWCs can exert positive effects on both citizen and police behavior."…”
Section: Literature Reviewmentioning
confidence: 71%
“…Since 2015, the U.S. Department of Justice (DOJ) has awarded nearly $60 million in grant funding to more than 250 law enforcement agencies to deploy BWCs (Bureau of Justice Assistance, ) . BWCs are widely supported across a diverse range of other key sectors including police leadership organizations (IACP, ), civil rights groups (e.g., the American Civil Liberties Union; Stanley, ), and citizens (Sousa, Miethe, and Sakiyama, ; White, Gaub, and Todak, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the findings from studies demonstrate reductions (see, e.g., Maskaly et al., ), it is still not clear that a properly implemented BWC program will reduce the use of force or complaints. The issue with targeting these outcomes using a body‐worn camera program is perhaps best identified in the earlier work of White, Gaub, and Todak (: 7) who reminded us that “the outcomes of interest are rare.” In small‐to‐mid‐sized departments, reductions in these events may be difficult to determine as there are so few incidents to measure. As such, these outcomes, although important, are not ideal for a program goal, as not achieving them may not be because of a problem with the BWC program.…”
Section: Goalsmentioning
confidence: 99%
“…Subsequently, there has been a host of high-quality, peer-reviewed scholarship that has further contributed to the BWC evaluation literature. Examples of this research include randomized controlled trials in Tempe, AZ (Gaub, Choate, Todak, Katz, and White, 2016), Spokane, WA (Gaub et al, 2016;White, Gaub, and Todak, 2017), and Las Vegas, NV (Braga, Sousa, Coldren, and Rodriguez, 2018); a host of randomized controlled trials in Europe (Ariel et al, 2016); rigorous quasi-experimental designs in Tampa, FL (Jennings, Fridell, Lynch, Jetelina, and Gonzalez, 2017), Mesa, AZ (Ready and Young, 2015), and Phoenix, AZ (Hedberg, Katz, and Choate, 2017); and several other methodologically sound studies in various jurisdictions (for a review, see Maskaly, Donner, Jennings, Ariel, and Sutherland, 2017).…”
mentioning
confidence: 99%